2014
DOI: 10.1371/journal.pone.0105617
|View full text |Cite
|
Sign up to set email alerts
|

Azvudine, A Novel Nucleoside Reverse Transcriptase Inhibitor Showed Good Drug Combination Features and Better Inhibition on Drug-Resistant Strains than Lamivudine In Vitro

Abstract: Azvudine is a novel nucleoside reverse transcriptase inhibitor with antiviral activity on human immunodeficiency virus, hepatitis B virus and hepatitis C virus. Here we reported the in vitro activity of azvudine against HIV-1 and HIV-2 when used alone or in combination with other antiretroviral drugs and its drug resistance features. Azvudine exerted highly potent inhibition on HIV-1 (EC50s ranging from 0.03 to 6.92 nM) and HIV-2 (EC50s ranging from 0.018 to 0.025 nM). It also showed synergism in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 41 publications
3
69
0
Order By: Relevance
“…Previous studies have demonstrated that FNC is a potent inhibitor of HIV, HCV and HBV replication (32,34,35,38). In this study, we evaluated the cytotoxicity and antiviral activities of FNC as well as its analogs against multiple EVs, including EV71, CA16, CA6, on September 26, 2020 by guest http://jvi.asm.org/ Downloaded from EVD68, and CVB3, and observed that FNC showed relatively low cytotoxicity toward RD cells (safe dose of 1 μM), HEK293T cells (safe dose of μM) and MDCK cells (safe dose of 10 μM) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that FNC is a potent inhibitor of HIV, HCV and HBV replication (32,34,35,38). In this study, we evaluated the cytotoxicity and antiviral activities of FNC as well as its analogs against multiple EVs, including EV71, CA16, CA6, on September 26, 2020 by guest http://jvi.asm.org/ Downloaded from EVD68, and CVB3, and observed that FNC showed relatively low cytotoxicity toward RD cells (safe dose of 1 μM), HEK293T cells (safe dose of μM) and MDCK cells (safe dose of 10 μM) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that FNC, a nucleoside inhibitor, could significantly inhibit HCV, HIV, and HBV replication by blocking viral DNA or RNA synthesis (32,34,35,38). Here, we investigated whether FNC and its 7 chemical analogs inhibit EV71 infection ( Fig.…”
Section: The Inhibitory Effect Of Fnc and Its Derivatives On Ev71 Repmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory effect of samples on acuteHIV-1 NL4-3 infection was measured by the syncytia formation assay as described previously 55 . In the presence or absence of various concentrations of compounds, Therapeutic index (TI) was calculated by the ratio of CC 50 /EC 50 .…”
Section: Inhibition Of Syncytia Formationmentioning
confidence: 99%
“…The inhibitory effect of samples on acuteHIV-1 NL4-3 infection was measured by the syncytia formation assay as described previously 55…”
Section: Inhibition Of Syncytia Formationmentioning
confidence: 99%